Mother and Offspring in Conflict: Why Not? - Úbeda, Francisco (Public Library of Science, 2015)
A gene mediating interactions between mouse mothers and their pups has recently been claimed to support coadaptation rather than the kinship theory of genomic imprinting. This Formal Comment argues that this claim is unfounded.